Study of cheiloscopy with the Renaud method in dentistry students of Tepic, Nayarit, Mexico, during the 2016-2017 school year - Marcela Rodríguez-Rucoba; Cheysy Anahí Álvarez-Puentes; Tania Villa-Jara; Jaime Fabián Gutiérrez-Rojo; Martha Patricia Guerrero-Castellón (Acta Odontológica Colombiana, 2018)
Background: the cheiloscopy is a technique of forensic stomatological individualization that classifies the labial traces contributing to the identity of a subject in both the civil and criminal areas. One of the most commonly used cheiloscopic classifications is Renaud´s, which classifies lip prints into 10 types. Objective: in Nayarit, there are no studies of stomatologic individualization, so the objective of this study was to identify the type of lip prints that prevail in dental students. Materials and methods: a descriptive cross-sectional study was carried out in a sample of 110 students between 18 and 24 years of age of the Unidad Académica de Odontología of the Universidad Autónoma de Nayarit, Mexico. Photographs were taken of the lips at a distance of 5 cm with Samsung camera dv150f, 16 mp and evaluated visually with the method of cheiloscopy by Renaud. Descriptive statistics were applied. Results: the grooves found with the highest prevalence were type G followed by type C and with less frequency type J. Conclusions: the labial trace is unique in each person, being the C type the second in prevalence, result that presents / displays similarity with populations of the American continent. It is recommended to do more studies in different groups of the mexican population.